Synergistic interaction of Curcuma longa with its microbiome: a mini review - Virk, Verinder; Deepak, Himani; Taneja , Khushbu (Journal of Postharvest Technology, 2023)
Curcuma longa L., popularly known as Haldi; member of Zingiberaceae family, is one of the most popular and useful herbal medicinal plant. The tremendous research proven that most of the medicinal properties of turmeric are due to the curcumin content in it. Turmeric has other various useful properties such as treatment of wounds, menstrual pain relief, antioxidants, anti-inflammatory, anticancerous, antiulcer, etc. Turmeric healthy rhizomes and roots are continuously in close association with the rhizospheric region and as a result, large number of rhizospheric-associated beneficial microbes interacts with the underground parts of plants. Soil microbes may neutralize the action of flavonoids released from the roots and get entry into the healthy tissues of plants to become endophytes. Rhizospheric and endophytic species either directly or indirectly involved in propounding beneficial impact to the plant. The present review emphasized in order to uncover the mutualistic association of turmeric and its associated microbes. Also the natural products from medicinal plant associated microbes have pharmacological, biological and therapeutic values which might favour mankind in future for drug designing and novel drug formulations.